THE PROVINCIAL GOVERNMENT POLICY OF JAMBI IN EFFORTS TO PRESERVE THE ANCIENT MANUSCRIPTS OF JAMBI MALAY - Saidina Usman; Nori Nopita Sari; Teguh Adimarta (Nizham Jurnal Studi Keislaman, 2021)
Jambi Province is one of the regions that has Malay culture as its original culture. Thehistorical background of Jambi Province is inseparable from the influence of the oldMalay kingdom, namely the Moloyu or Malay kingdom. This historical backgroundmakes the Jambi provincial government want to maintain and make Malay culture alocal culture and become a regional identity. Therefore, the Jambi provincialgovernment in 2013 together with the Jambi Provincial DPRD signed RegionalRegulation number 7 of 2013 concerning the preservation and development of JambiMalay culture. In addition, the government's steps and good intentions to developculture also have a strong legal umbrella, namely the 1945 Constitution. This articlewill focus on analyzing the implementation of Perda number 7 of 2013, which containsthe policy of the Jambi provincial government in trying to preserve Jambi Malay texts.Based on field observations, interviews, reading archives and documents related to theimplementation of the mandate of perda number 7 of 2013, this article argues that thepolicy on preserving ancient manuscripts, which is the super important local wealthand wisdom of the Jambi people, has not been fully implemented by the related LeadingSector. So this confirms that the government and society's awareness andunderstanding of the importance of preserving the ancient Jambi Malay manuscriptsis still low. This article argues that the policy on preserving ancient manuscripts,which is the super important local wealth and wisdom of the Jambi people, has not beenfully implemented by the relevant Leading Sector. So this confirms that the governmentand society's awareness and understanding of the importance of preserving the ancientJambi Malay manuscripts is still low. This article argues that the policy on preservingancient manuscripts, which is the super important local wealth and wisdom of theJambi people, has not been fully implemented by the relevant Leading Sector. So thisconfirms that the government and society's awareness and understanding of the importance of preserving the ancient Jambi Malay manuscripts is still low.